Refleksi Ajaran Shinto Dalam Omamori - Yuliani Rahmah (Diponegoro University, 2019)
(Title: Shintoism Reflection InOmamori) Shinto handed down from generation to the next generation. Shintoism have had a strong influence on the lives of Japanese people, from festival activities to objects in their surroundings. Omamori is known as one form of that influence and became a culture part of the harmonization of the Shintoism and Buddhism. As one of the sacred objects which are still trusted by Japanese people, the existence of omamori is so popular even in modern society. Through a literature review, this article aims to describe what parts of the omamori are a reflection of Shintoism. The results obtained show that the reflection can be seen among others in the omamori user's belief in the existence of kamisama (Gods), and evil spirits, also can be seen from the material of the omamori itself.